Adaptive Responses and Differences in Morphophysiological Resistance of Dendrobium sp., Phalaenopsis sp., and Vanda sp. Orchids to Abiotic Stress - Moch. Faizul Huda; Ospa Pea Yuanita Meishati; Rossanita Truelovin Hadi Putri; Ahmad Sahal Mahfudz (El-Hayah:Jurnal Biologi, 2026)
Orchids are an important horticultural commodity in Indonesia with high economic and conservation value; however, their sustainability is threatened by abiotic stress, such as salinity. This study aims to screen the resistance of Dendrobiumsp., Phalaenopsis sp., and Vanda sp. to NaCl salinity stress. The study used a completely randomized design (CRD) with three replications. The treatment, in the form of giving 1%, 5%, and 10% NaCl, was compared with the control. The morphological response and physiological content, including chlorophyll content (mg/L), were then observed. The results showed that chlorophyll content decreased significantly with increasing NaCl concentration. Total chlorophyll of Phalaenopsis sp. decreased sharply with increasing NaCl concentration from 5.25 mg/L (control), 3.78 mg/L (1%), 1.74 mg/L (5%) and 0.54 mg/L (10%); In contrast to Dendrobium sp. which showed fluctuations from 5.02 mg/L (control), 8.20 mg/L (1%), 3.74 mg/L (5%) and 4.05 mg/L (10%). While Vanda sp. experienced a moderate decrease from 9.42 mg/L (control), 9.41 mg/L (1%), 4.53 mg/L (5%), and 4.26 mg/L (10%). The relative resistance order was Vanda sp.  Dendrobium sp.  Phalaenopsis sp. Phalaenopsis sp. was the most susceptible plant to salinity, with a sharp decrease in chlorophyll and severe morphological symptoms of the necrotic type, while Vanda sp. showed the most tolerant response with a smaller decrease in chlorophyll. In general, NaCl has been shown to drastically suppress chlorophyll content and is a significant limiting factor for the sustainability of orchid cultivation.